2020
DOI: 10.14529/jsfi200305
|View full text |Cite
|
Sign up to set email alerts
|

In Search of Non-covalent Inhibitors of SARS-CoV-2 Main Protease: Computer Aided Drug Design Using Docking and Quantum Chemistry

Abstract: Two stages virtual screening of a database containing several thousand low molecular weight organic compounds is performed with the goal to find inhibitors of SARS-CoV-2 main protease. Overall near 41000 different 3D molecular structures have been generated from the initial molecules taking into account several conformers of most molecules. At the first stage the classical SOL docking program is used to determine most promising candidates to become inhibitors. SOL employs the MMFF94 force field, the genetic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Relying upon results of docking and quantum chemical calculations of the protein–ligand binding enthalpy, the analysis of the docked ligand poses in the protein active site, and providing the chemical diversity of the ligands, we selected a series of compounds for the first experimental testing [ 38 ]. All these ligands blocked the catalytic dyad of the SARS-CoV-2 M in their docked conformations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Relying upon results of docking and quantum chemical calculations of the protein–ligand binding enthalpy, the analysis of the docked ligand poses in the protein active site, and providing the chemical diversity of the ligands, we selected a series of compounds for the first experimental testing [ 38 ]. All these ligands blocked the catalytic dyad of the SARS-CoV-2 M in their docked conformations.…”
Section: Resultsmentioning
confidence: 99%
“…The calculated and measured characteristics of the three active compounds ( 3a , 6a , 9a ) determined among the first set of 18 compounds selected for experimental testing [ 38 ] are presented in Table 1 . These characteristics are: the estimate of the free energy of protein–ligand binding calculated by SOL (SOL score), the protein–ligand binding enthalpy , as well as the 50% effective concentrations (EC ) of the compounds that inhibit the viral replication the cell culture and the selectivity index .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the controversy increases because ivermectin has been included in clinical trials that have shown promising results ( Carvallo and Hirsch, 2020 ) ( https://clinicaltrials.gov/ct2/show/NCT04425863 - ClinicalTrials.gov Identifier: NCT04425863) and in collective reviews of multiple efforts that have suggested that ivermectin may have a prophylactic effect and would be a strong candidate for clinical trials to treat SARS-CoV-2 ( Low et al, 2022 ), as also observed in systematic reviews and meta-analyses of randomized clinical trial studies ( Hariyanto et al, 2022 ). In addition, general descriptions of the possible mechanisms of action have been provided based on experimental and computational studies that have suggested a multi-target mechanism of ivermectin against SARS-CoV-2 ( Tang and Dill, 1998 , Tang and Kaneko, 2020 ).…”
Section: Resultsmentioning
confidence: 99%